2021
DOI: 10.1093/dote/doab089
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiotherapy, chemotherapy, and radiotherapy do not significantly increase the incidence of anastomotic leakage after esophageal cancer surgery: a meta-analysis

Abstract: Summary This study investigated whether neoadjuvant therapies, such as neoadjuvant chemoradiotherapy (NCRT), neoadjuvant chemotherapy (NCT), and neoadjuvant radiotherapy (NRT), would affect the incidence of anastomotic leakage (AL) after esophageal cancer surgery. Published randomized controlled trials were reviewed, and the incidence of AL after esophageal cancer was statistically analyzed in each study. Meta-analysis was performed using Revman and Stata software. A total of 17 randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Therefore, it is very important to accurately evaluate the preoperative staging of patients. For esophageal cancer patients, accurate preoperative staging is helpful to provide the most appropriate individualized treatment plan for these patients (6)(7)(8)(9)(10). For example, some patients with preoperative stage T4 can increase the chance of radical resection through neoadjuvant therapy (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to accurately evaluate the preoperative staging of patients. For esophageal cancer patients, accurate preoperative staging is helpful to provide the most appropriate individualized treatment plan for these patients (6)(7)(8)(9)(10). For example, some patients with preoperative stage T4 can increase the chance of radical resection through neoadjuvant therapy (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative complications have always been an area of concern in EC. Jin et al ( 28 ) found in a meta-analysis that nCRT and neoadjuvant radiotherapy (NRT) did not significantly increase the risk of postoperative anastomotic leak in EC patients. nCRT has attracted a great deal of attention.…”
Section: Definition and Progress Of Neoadjuvant Therapy For Esophagea...mentioning
confidence: 99%
“…Some studies indicated that neoadjuvant chemotherapy, particularly in combination with radiotherapy, is associated with increased surgical complication risk in patients with oesophageal cancer undergoing resection surgery. However, a meta-analysis of 17 randomised controlled trial (RCT)s, including more than 2800 patients, determined that neither neoadjuvant chemotherapy nor chemoradiotherapy were associated with increased risk of anastomotic leakage, a complication of particular concern among surgeons performing oesophageal resection surgery [32]. Other studies have drawn specific attention to increased incidence of pulmonary complications and vocal cord paralysis, although data from a second meta-analysis of 18 studies failed to demonstrate any statistically significant increase in risk for any of the included complications [33].…”
Section: Neoadjuvant Chemotherapy: Is There Significant Risk?mentioning
confidence: 99%